The three-body problem - Liu, Cixin (Tor Books, 2014)
"With the scope of Dune and the commercial action of Independence Day, this near-future trilogy is the first chance for English-speaking readers to experience this multple-award-winning phenemonenon from China's most beloved science fiction author. Set against the backdrop of China's Cultural Revolution, a secret military project sends signals into space to establish contact with aliens. An alien civilization on the brink of destruction captures the signal and plans to invade Earth. Meanwhile, on Earth, different camps start forming, planning to either welcome the superior beings and help them take over a world seen as corrupt, or to fight against the invasion. The result is a science fiction masterpiece of enormous scope and vision"--